Education Effects on Job-Related Constructs Among Frontline Employees in the Hotel Industry - Marija Cimbaljevic; Dunja Demirovic Bajrami; Sanja Kovacic; Ivana Blesic; Tatjana Pivac (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2023)
To make tourism enterprises functioning harmonious and in order to achieve good business results, knowledgeable, engaged, service-oriented, and therefore satisfied staff is crucial, because human resources are one of the most important segments of the service quality in the tourism and hospitality industry. The study explored moderating effects of education on relationships between service orientation and work engagement on employees’ job satisfaction among employees in the hotel industry in Serbia. Moderating effects of education are particularly noticeable between service orientation and job satisfaction. Also, the results indicated that employees who had a high school degree showed the lowest level of job satisfaction, as well as service orientation and work engagement. On the other side, employees who have tourism education indicated less job satisfaction, service orientation and work engagement. Based on the insight into the employees' attitudes and behavior, managers can organize various training programs especially for employees with lower education level, in order to remove any obstacles in their work, to motivate them more and improve working conditions.